Description of the larva of the genus Archaeopodagrion Kennedy, 1939 (Zygoptera: Philogeniidae) - Novelo-Gutiérrez, Rodolfo; Bota-Sierra, Cornelio Andrés; Amaya-Vallejo, Vanessa (Zootaxa, 2020)
The larva of Archaeopodagrion fernandoi Bota-Sierra, 2017, is described and illustrated in detail, being the first larva described for the genus Archaeopodagrion. The description is based on F-0 larvae collected from the type locality. The larva of A. fernandoi shows great resemblance to larvae of Philogenia spp., which adds support to the hypothesis of the monophyletic family Philogeniidae which groups together Archaeopodagrion and Philogenia. However, both genera differ each other by the presence of basal, spiny, fleshy tubercles on caudal lamellae of Archaeopodagrion.